2020
DOI: 10.1111/jfbc.13390
|View full text |Cite
|
Sign up to set email alerts
|

Structure characteristics of flavonoids for heterocyclic aromatic amines inhibition using quantitative structure–activity relationship modeling

Abstract: The objective of this study was to investigate the structure characteristics of flavonoids that act as inhibitors for heterocyclic aromatic amines (HAAs) formation. Five quantitative structure–activity relationship models for predicting the inhibitory rates of HAAs (norharman, harman, PhIP, MeIQx, and 4,8‐DiMeIQx) were established using selected chemometric parameters (R2: 0.591–0.920), and indicated that the hydrophobicity, hydroxyl groups, and topological structure of flavonoids played important roles in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 34 publications
(46 reference statements)
0
16
0
Order By: Relevance
“…Specifically, the correlation coefficients between mean DP and individual HCAs were −0.799 for PhIP, −0.758 for harman and −0.697 for norharman, indicating that the mean DP significantly affects ( P < 0.05) the formation of HCAs. Proanthocyanidins with lower DPs could reduce HCAs due to the presence of more nucleophilic sites which benefit adduct formation (Zhao et al ., 2020). The result showed a negative linear dependent relationship between antioxidant abilities and HCA inhibition (Table 5), but none of them were significant ( R 2 < −0.370, P > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the correlation coefficients between mean DP and individual HCAs were −0.799 for PhIP, −0.758 for harman and −0.697 for norharman, indicating that the mean DP significantly affects ( P < 0.05) the formation of HCAs. Proanthocyanidins with lower DPs could reduce HCAs due to the presence of more nucleophilic sites which benefit adduct formation (Zhao et al ., 2020). The result showed a negative linear dependent relationship between antioxidant abilities and HCA inhibition (Table 5), but none of them were significant ( R 2 < −0.370, P > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of single compounds, many algorithms have been developed that help in the theoretical determination of the activity spectrum. Based on the QSAR analysis, the physical and chemical properties of compounds are calculated and their bioavailability and biological activity are estimated [ 15 , 16 ]. It has been found that lipophilicity is one of the most important physicochemical properties that influences the biological activity of compounds [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ability of epicatechin to mitigate HA formation may also be related with its scavenging capacities of the free radical and reactive carbonyl, which are highly related to the formation of HAs . Zhao also reported that 10 mM epicatechin exhibited 44.01, 31.13, and 78.04% inhibitory effects on the formation of PhIP, Harman, and Norharman, respectively, in the chemical model system that was heated at 175 °C for 30 min.…”
Section: Resultsmentioning
confidence: 99%
“… The establishment of chemical model systems of PhIP, Harman, and Norharman was carried out according to the literature with slight modifications. , Briefly, for PhIP, 0.4 mmol phenylalanine, 0.4 mmol creatinine, 0.4 mmol glucose, and 0.2 mmol epicatechin were added into 25 mL screw cap-sealed reaction vials (Strg Vial Kit, 40 mL, 28 × 95 Amber, 24-414 Cap, Agilent, USA); then, 4 mL of diethylene glycol containing 14% of distilled water was added, and citric acid-phosphate buffer was used to adjust the pH of the mixed solution using a pH meter (FE28-Micro, Mettler Toledo, Switzerland) under magnetic stirring (EMS-19, Tianjin Honour lnstrument Co., Ltd., China), which was finally stirred evenly. For Harman and Norharman, 0.4 mmol tryptophan, 0.4 mmol glucose, and 0.2 mmol epicatechin were put into 25 mL screw cap-sealed reaction vials; then, 4 mL of diethylene glycol containing 14% of distilled water was added, and citric acid-phosphate buffer was used to adjust the pH of the mixed solution, which was finally stirred evenly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation